2016
DOI: 10.1002/anie.201606060
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐Origami‐Based Multiplexed Malaria Diagnostics from Whole Blood

Abstract: We demonstrate, for the first time, the multiplexed determination of microbial species from whole blood using the paper‐folding technique of origami to enable the sequential steps of DNA extraction, loop‐mediated isothermal amplification (LAMP), and array‐based fluorescence detection. A low‐cost handheld flashlight reveals the presence of the final DNA amplicon to the naked eye, providing a “sample‐to‐answer” diagnosis from a finger‐prick volume of human blood, within 45 min, with minimal user intervention. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 28 publications
0
98
0
Order By: Relevance
“…Examples of these products are FTAcard, [16][17][18][19][20][21][22] chitosancoated paper, [23,24] glass-fiber paper, [25][26][27][28] and polyethersulfone filter paper. Examples of these products are FTAcard, [16][17][18][19][20][21][22] chitosancoated paper, [23,24] glass-fiber paper, [25][26][27][28] and polyethersulfone filter paper.…”
mentioning
confidence: 99%
“…Examples of these products are FTAcard, [16][17][18][19][20][21][22] chitosancoated paper, [23,24] glass-fiber paper, [25][26][27][28] and polyethersulfone filter paper. Examples of these products are FTAcard, [16][17][18][19][20][21][22] chitosancoated paper, [23,24] glass-fiber paper, [25][26][27][28] and polyethersulfone filter paper.…”
mentioning
confidence: 99%
“…Isothermal strand displacement amplification is employed utilizing Bst DNA polymerase, which can simultaneously achieve double‐stranded DNA (dsDNA) displacement and primer extension at a constant temperature . The isothermal amplification strategy avoids the need of thermal cyclers and can be easily integrated with other technologies, which is suitable for point‐of‐care testing applications . On the other hand, we have introduced carbon nanodots (CDs), a new class of carbon nanomaterials, as the fluorescent sources in this biosensor .…”
Section: Methodsmentioning
confidence: 99%
“…However, PCR-based assays are poorly suited to perform in field settings as they require specialized equipment for sample preparation and skilled personnel (Britton et al, 2016b). Alternative NATs, such as loop-mediated isothermal amplification (LAMP) assays (Abdul-Ghani, 2014; Goyal et al, 2015; Han, 2013; Hsiang et al, 2014; Morris et al, 2015; Oriero et al, 2015; Patel et al, 2014; Sattabongkot et al, 2014; Singh et al, 2013; Sirichaisinthop et al, 2011; Surabattula et al, 2013), recombinase polymerase amplification (RPA) assays (Cordray and Richards-Kortum, 2015; Kersting et al, 2014), as well as helicase dependent amplification (HAD) assays (Li et al, 2013) have shown high analytical sensitivity and great potential for field deployment by integrating with microfluidic (Liu et al, 2016) and paper based devices (Xu et al, 2016). Among isothermal methods, LAMP is the most studied assay for malaria detection and holds great promise for commercialization.…”
Section: Introductionmentioning
confidence: 99%